Digital marketing in hotel industry - Javed Parvez, Shaik; M. Moyeenudin, H; Arun, S; Anandan, R; Kumar Janahan, Senthil (International Journal of Engineering and Technology, 2018)
Digital marketing is the promotion of products or brands through online. In recent days the demand of digital marketing in hotels has become increasingly high with Social Media Marketing (SMM) which works with social networking sites and Search Engine Optimization (SEO) making the website to appear in search results with advertisement on Google and online magazines by search engine marketing (SEM), video marketing through you tube and websites are types of digital marketing. Searching hotels through online by computers and mobile with the hotel websites is the new trend of digital marketing and it makes the possibilities to enhance the local search on hotels by giving required content, User profiles, managing citations and in search results. The aim is to study the role of digital marketing in hotel industry. This article is also focused to identify which type of digital marketing will work best with hotel industry.Â Â